The Libya Intervention (2011): Neither Lawful, nor Successful - Terry, Patrick (Comparative and International Law Journal of Southern Africa, 2022)
The intervention in Libya in 2011 was claimed to have been a triumph intwo respects: on the one hand the UN Security Council, by passing resolutions 1970 and 1973, had demonstrated its ability to react to humanitarian crises without any of the five permanent members of the council resorting to a veto. On the other hand the concept of humanitarian intervention in its more recent guise of the “responsibility to protect” was seen by some as having finally gained recognition within the international community as a legal concept. More than three years after the intervention it will be argued here that such optimistic claims were premature. It will be shown that the way a coalition of NATO and other states implemented resolution 1973 was not in accordance with that resolution and therefore violated international law. As a direct consequence of this, the Security Council has now reverted to its former paralysis, as Russia and China are, understandably, no longer willing to grant NATO states a mandate for action. This has been most evident in respect of the civil war in Syria. Moreover, developments in Libya since the intervention have done more to discredit the concept of the “responsibility to protect” than any criticism from an international law perspective possibly could.